Nursing Care for Dengue Fever Patient in the Critical Phase, at a Hospital in West Jakarta - Nurhasanah; Ernawati; Permaida; Stepanus Maman Hermawan (Jurnal Keperawatan Priority, 2025)
Dengue Haemorrhagic Fever is a disease caused by the dengue virus due to the bite of the Aedes aegypti mosquito. Patients will go through 3 phases of this disease: fever, critical, and recovery. A complication that often occurs in the critical phase is dengue shock syndrome. This case report aimed to provide an overview of nursing care for patients in the critical phase of dengue hemorrhagic fever at a private hospital in West Jakarta. Care was provided by Diploma III nursing students for 4 days using a nursing process approach that includes assessment, diagnosis, planning, implementation, and evaluation. Data was collected using interview techniques, observation, and physical and diagnostic examinations. The assessment showed that the patient was in a grade II critical phase, characterized by the appearance of petechiae on both superior extremities without a tourniquet test. The nursing problems raised were the risk of hypovolemia, the risk of bleeding, acute pain, and nausea. The interventions provided focus on preventing bleeding and fluid management. The implementation includes providing appropriate fluid resuscitation, monitoring blood hematology laboratories, and encouraging patients to rest in bed to reduce the risk of other bleeding. On the fourth day of treatment, three nursing problems were solved: the risk of bleeding, acute pain and nausea. The nursing problem that was partially resolved is the risk of hypovolemia. In conclusion, in dengue hemorrhagic patients in the critical phase, nurses need to pay primary attention to the possibility of hypovolemia even though it is not necessarily an actual problem.